The prevalence of smart phone addiction among students in medical sciences universities in Tehran 2016 - Yahyazadeh, Simin; Fallahi-Khoshknab, Masoud; Norouzi, Kiyan; Dalvandi, Asghar (Advances in Nursing & Midwifery, 2017)
Abstract Background and Aim: The use of smartphone technology has made significant development during recent years. The use of this technology in students' growth rate was higher. Besides the advantages of this technology, such as drug side effects may also occur. Despite the impairment nursing student safety and patient care is difficult. This study aimed to assess the prevalence of smart phone addiction among students of Tehran University of Medical Sciences. Materials and Methods: This study was a cross-sectional study was conducted between April and June 1395. The study has been conducted on 150 nursing students of Tehran University of Medical Sciences. Quota cluster sampling was done. The research instrument was kwon questionnaire smart phone addiction. The questionnaire was returned by forward-backward translation in Farsi. The data were analyzed by independent t-test and Chi-square. SPSS-16 Software was used for analysis. Results: The mean smart phone addiction among students was 12.77 ± 32.94. 9.3% of students were addicted to the smart phone addiction. Between the hours of use of smart phones and Internet access and there is a single smart phone addiction (p <0.05). Conclusion: Smartphone addiction among students with prevalence was nearly ten percent. There is access to the Internet and the increased use of smart phones is associated with the disorder. The use and how to use smart phones in educational environments and health should be controlled. Keywords: Addiction, Smartphone, Nursing students